(untitled) (Fourth World Journal, 2023)
On August 8, 2022, in anticipation of an important meeting of the leadership of the National Congress of American Indians, the Chairman of the Center for World Indigenous Studies wrote a brief letter to the President of the National Congress of American Indians. The letter was a product of earlier discussions between the Chairman and the President of the two organizations. The central thesis of the letter is a discussion of the emergent political dangers to tribal sovereignty in the United States and elsewhere in the world. The letter discussed the “five horsemen of the Apocalypse. Over the six months since the letter was written, new information became available and is now included in the updated letter. We publish its content in the Fourth World Journal to encourage a broader understanding of the challenges faced by indigenous peoples in the United States and other countries.